Bacterial IsolateProfile in Gram-Negative Urinary Isolates: Role ofNitrofurantoin - Sharma, Meghna; Soneja, Sapna; Oberoi, Loveena; Malhotra, Anuradha; Singh, Kamaldeep; Mahindroo, Babica (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: In current times epidemic drug resistance has renewed interest in drugs belonging to the yesteryears, most importantly Nitrofurantoin for urinary tract infections. Studies have reported that more than 90% of urinary tract infections are due to enteric Gram-negative organisms, of which more than 80% are E.coli. Objectives: To study bacterial profile in Gram-negative urinary isolates and evaluate the role of nitrofurantoin. Methods:We retrospectively evaluated 500 consecutive Gram-negative bacterial isolates for bacteriological profile and nitrofurantoin sensitivity of patients of urinary tract infections at a tertiary care facility in Indiabetween January and June of 2022. Results:We had a total of 500 Gram- negative urinary isolates. 383 (76.6%) of these were found to be susceptible to nitrofurantoin. E. coli alone constituted 343 (68.6%) of total 500 Gramnegative isolates, 264 (76.96%) of which were sensitive to nitrofurantoin. 20 (4%) Proteus and 05 (1%) Citrobacter species were isolated and found to be resistant to nitrofurantoin. 12 (80%) out of the 15 Acinetobacter isolates were resistant to nitrofurantoin. All 12 (100 %) Pseudomonas isolates tested resistant to nitrofurantoin. Conclusion:E. coli is the most common of uropathogens and despite rise in antibiotic resistance, it continues to be sensitive to nitrofurantoin. Resistance to nitrofurantoin is also being reported and this calls for judicious further use of this drug based on culture reports and local prevalence data. International Journal of Human and Health Sciences Vol. 07 No. 02 Apr’23 Page: 162-165